Social Hermeneutics Study On the Meaning of Jihad by Students of Mulawarman University: Studi Hermeneutika Sosial Tentang Makna Jihad Menurut Mahasiswa Universitas Mulawarman - Saputra, Langgeng; Murlianti, Sri; Nanang, Martinus (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
ABSTRACT: Jihad has been an integral part of Islamic discourse from its early days until today. This research was conducted to determine variations in the meaning of jihad that developed in Mulawarman University students. I use Paul Ricoeur's theory of Social Hermeneutics to explain how the process of interpreting meaning from a text. Ricoeur views that text has a life of its own regardless of the author's intention or intent (text autonomy). In interpreting the text, Ricoeur also argues that understanding and explanation are not two contradictory methods of interpreting the text. The workings of Paul Ricoeur's social hermeneutics include three factors, namely the world of text, the world of presenters, and the world of readers, whereas in this paper there are only two factors, namely the world of text and the world of readers. Jihad in al-Qur'an is repeated 41 times in 23 verses and by Ibn Al-Qayyim it is divided into four meanings, namely jihad against lust, jihad against Satan, jihad against infidels, and hypocrites, and jihad against injustice and wickedness. Meanwhile, readers only divide jihad into two meanings, namely jihad against lust and war jihad. In the process of interpreting, readers are greatly influenced by the trajectories of life that they have been through. This can be seen from the many meanings of jihad they express, namely war, defending, doing good, effort/strength, being serious, preaching, and enthusiasm. ABSTRAK: Jihad merupakan bagian integral wacana Islam sejak masa awal kedatangannya hingga sampai saat ini. Penelitian ini dilakukan untuk mengetahui variasi makna jihad yang berkembang pada Mahasiswa Universitas Mulawarman. Teori Paul Ricouer tentang Hermenutika Sosial saya gunakan untuk menjelaskan tentang bagaimana proses menafsir sebuah makna dari sebuah teks. Ricouer berpandangan bahwa teks memiliki kehidupannya sendiri terlepas dari intensi atau maksud pengarang (otonomi teks). Dalam menginterpretasi teks, Ricoeur juga berpendapat bahwa pemahaman dan penjelasan bukanlah dua metode yang bertentangan dalam menafsirkan teks. Cara kerja hermenutika sosial Paul Ricoeur mencakup tiga faktor yaitu dunia teks, dunia pemateri dan dunia pembaca sedangkan dalam tulisan ini hanya ada dua faktor yaitu dunia teks dan dunia pembaca. Jihad dalam al-Qur’an terulang 41 kali dalam 23 ayat dan oleh Ibn Al-Qayyim dibagi menjadi empat makna, yakni jihad melawan hawa nafsu, jihad melawan setan, jihad memerangi kaum kafir dan kaum munafik serta jihad melawan kezaliman dan kefasikan. Sedangkan pembaca hanya membagi jihad dalam dua makna yakni jihad melawan hawa nafsu dan jihad perang. Dalam proses penafsirannya, pembaca sangat dipengaruhi oleh trajektori kehidupan yang mereka pernah lalui. Hal ini dapat dilihat dari banyaknya makna jihad yang mereka ungkapkan, yaitu perang, membela, melakukan kebaikan, usaha/kekuatan, bersungguh-sungguh, dakwah serta semangat.